Oxidative stress status in congenital hypogonadism: an appraisal. (24th July 2017) - Haymana, C.; Aydoğdu, A.; Soykut, B.; Erdem, O.; Ibrahimov, T.; Dinc, M.; Meric, C.; Basaran, Y.; Sonmez, A.; Azal, O.
Abstract: Patients with hypogonadism are at increased risk of cardiac and metabolic diseases. However, the pathogenesis of increased cardiometabolic risk in patients with hypogonadism is not clear. Oxidative stress plays an important role in the pathogenesis of cardiometabolic diseases. This study aimed to investigate possible differences in oxidative stress conditions between patients with hypogonadism and healthy controls. In this study, 38 male patients with congenital hypogonadotropic hypogonadism (CHH) (mean age: 21.7 ± 1.6 years) and 44 healthy male controls (mean age: 22.3 ± 1.4 years) with almost equal body mass index were enrolled. The demographic parameters, follicle-stimulating hormone (FSH), luteinizing hormone (LH), total and free testosterone, homeostatic model assessment of insulin resistance (HOMA-IR) and oxidative stress parameters, such as superoxide dismutase, catalase (CAT), glutathione peroxidase (GPx) and malondialdehyde (MDA), were compared between both groups. Compared to the healthy controls, triglycerides ( p  = .02), insulin levels, HOMA-IR values, CAT activities and MDA levels ( p  < .001 for all) were significantly higher and HDL cholesterol ( p  = .04), total and free testosterone, FSH, LH levels and GPx activity were significantly lower ( p  < .001 for all) in patients with CHH. There were significant correlations between total testosterone levels and CAT activity ( r  = −.33 p  = .01), GPx activity ( r  = .36 p  = .007) and MDA ( r  = −.47 p  < .001) levels. The results of this study showed that young and treatment-naïve patients with congenital hypogonadism had an increased status of oxidative stress.